Legal and judicial ethics - Bernardo, Oscar B. (Philippines; National Book Store, 2006)
Legal and Judicial Ethics collectively is a practical science because the precepts of the subject are actually rules of conduct supposed to be observed by the members of the legal profession in the exercise or practice of the profession inclusive of the members of the profession who are "sitting on bench(3y (Bas judges or justices, hence the subject Legal and Judicial Ethics.s